Implementasi Nilai-Nilai Multikultural Pada Pembelajaran Sejarah Kelas X Di SMA Muhammadiyah 1 Pontianak - Sulistyarini, Sulistyarini; Chalimi, Ika Rahmatika; Sari, Intan Novita (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this research is to explain the implementation of multicultural values in class X history learning at SMA Muhammadiyah 1 Pontianak. The method used descriptive method with qualitative research type. The data sources were two history teachers, one deputy head of curriculum, one deputy head of student affairs and al-islam kemuhammadiyahan and sixteen grade X students. Data collection techniques and tools used observation with observation guides, interviews with interview guides and documentation. Data analysis techniques used data reduction, data presentation and conclusion drawing. The results showed (1) The situation and conditions of diversity in SMA Muhammadiyah 1 Pontianak are well maintained so as to minimize the occurrence of cultural divisions or conflicts in the school environment. (2) The process of implementing multicultural values in class X history learning at SMA Muhammadiyah 1 Pontianak is carried out by delivering learning materials by teachers using lecture, question and answer, discussion and evaluation learning methods. (3) The obstacles experienced by teachers in implementing multicultural values in class X history learning at SMA Muhammadiyah 1 Pontianak are that there are some students who are still passive in participating in history learning and do not understand what is meant by multicultural and its values.